A preliminary study of oral liquid by 1H and 13C NMR spectroscopy (LLC "Endo Press", 2020)
In dentistry, the implementation of the principles metabolomics is just beginning, and obviously has a great future. One of the goals of metabolomics is the early diagnosis of disease at a stage when they may not have clinical manifestations. clinical examination of patients was carried out, men and women, aged from 18 to 30 years. Particular attention was paid to the detection of wedge-shaped defects of teeth hard tissues at various stages of this disease, as well as co-factors of its occurrence. Laboratory test method was selected nuclei magnetic resonance spectroscopy of proton and carbon nuclear isotope sample liquid oral healthy person (control) and patients with severe defects tapered teeth. The data show that the spectroscopy makes it possible to determine the concentration and composition of the low molecular weight organic substances in samples of saliva, which will serve as a subject for further research.